The effect of phacoemulsification performed with vitrectomy on choroidal vascularity index in eyes with vitreomacular diseases - Heejeong Chun (Nature Portfolio, 2021)
Abstract This study evaluated the effects of cataract surgery combined with pars plana vitrectomy (ppV) on choroidal vascularity index (CVI) in eyes with epiretinal membrane (ERM) and full thickness macular hole (FTMH). Medical records of 132 eyes with ERM or FTMH were retrospectively reviewed and classified into a ppV group and a ppV combined with cataract surgery group (phaco + ppV group). The CVI were measured at baseline, 1, 3 and 6 months after the surgery, using the selected swept-source (SS) optical coherence tomography (OCT) scan passing through the central fovea, which was then segmented into luminal and stromal area by image binarization. The mean CVI of phaco + ppV group were 61.25 ± 1.97%, 61.66 ± 1.81%, and 62.30 ± 1.92% at baseline, 1 and 3 months, respectively (p < 0.001). The mean CVI of ppV group were 62.69 ± 1.92%, 62.03 ± 1.51%, and 61.45 ± 1.71% at baseline, 1 and 3 months, respectively (p < 0.001). The final CVI were measured at 6 months and compared with the baseline CVI. The mean CVI of phaco + ppV group were 61.21 ± 1.99% at baseline and 60.68 ± 2.02% at 6 months (p < 0.001). The mean CVI of ppV group were 62.93 ± 1.70% at baseline and 61.77 ± 1.74% at 6 months (p < 0.001). Vitrectomy significantly decreases CVI in vitreomacular diseases possibly due to the removal of vitreomacular traction or postoperative oxygenation change in the eye. On the contrary, combined surgery of vitrectomy and cataract surgery significantly increases CVI in the early stage of postoperative period, which suggests choroidal vascular dilatation or congestion due to postoperative inflammation. Although the CVI were measured lower than the baseline in the end, more thorough inflammation control may be essential after combined surgery.